Parental attachment and truant rationalizations of antisocial behavior: findings from a randomized controlled trial - Cardwell, Stephanie M. (Journal of crime and justice, 2020)
Theorists propose that young people are likely to offend when they rationalize antisocial behavior and that pro-social attachments to parents might modify this relationship. This research first assesses whether or not a truancy reduction program is able to modify the effects of a young person’s rationalizations on antisocial behavior and then explores if parental attachments impact this relationship. Data are from the Ability School Engagement Program (ASEP), a third-party policing intervention designed to reduce truancy and crime by increasing parental knowledge of education laws in a sample of 102 high truanting youth from Brisbane, Australia. The conferences also incoorporated restorative and reintegrative shaming practices, which have previously been theorized to impact rationalizing behaviors. We find that post-intervention measures of rationalizations are positively related to self-reported antisocial behavior for those in the experimental condition. The impact of rationalizations on antisocial behavior varied at different levels of parental attachment only for the experimental group, as the effect of rationalizations on antisocial behavior became stronger at higher levels of parental attachments. We conclude that those in the experiment with strong parental attachments may have used more rationalizations to engage in antisocial behavior to overcome some of the pro-social effects of the ASEP intervention.